Toward a robust architecture for the regulation of data and digital trade - Dan Ciuriak; Marija Ptashkina (Centre for International Governance Innovation (CIGI), 2020)
The rapid digital transformation occurring worldwide poses significant challenges for policy makers working within a governance framework that evolved over centuries. Domestic policy space needs to be redefined for the digital age, and the interface with international trade governance recalibrated. In this paper, Dan Ciuriak and Maria Ptashkina organize the issues facing policy makers under the broad pillars of "economic value capture," "sovereignty" in public choice and "national security," and outline a conceptual framework with which policy makers can start to think about a coherent integration of the many reform efforts now under way, considering how policies adopted in these areas can be reconciled with commitments under a multilateral framework adapted for the digital age.
Keywords: 330